A large-scale study of microplastic abundance in sediment cores from the UK continental shelf and slope. (May 2022) - Kukkola, A.T.; Senior, G.; Maes, T.; Silburn, B.; Bakir, A.; Kröger, S.; Mayes, A.G.
Abstract: To inform risk assessments, reliable, time efficient and affordable quantification methods are required for creating a microplastic (MP) pollution baseline in the world's oceans. To facilitate this, MP abundance was investigated in sediments of three contrasting areas of the UK continental shelf: North West of Jones Bank, the Canyons in the Celtic Sea and Dogger Bank in the North Sea, utilising the Nile Red tagging method to assess its time efficiency and cost. Average MP abundance in the top 10 cm was 1050–2700 MP kg −1 . MP abundance decreased with increasing sediment depth and increased with increasing water depth. The findings emphasise the extent of MP pollution and illustrate the value of Nile Red for large scale mapping at relatively low cost. Graphical abstract: Unlabelled Image Highlights: Three different areas of the UK continental-shelf were investigated for microplastics. Microplastic abundance increases with water depth and decreases with depth into the sediment. Microplastic abundance in UK sediments could be as high as 2700 MP kg −1 . Nile Red offers a rapid and low-cost approach to monitoring microplastics on a large scale.